Modernisme Dalam pandangan Maryam Jameelah - Amiri, Bustom; , Dr. Sudarno Shobron, M.Ag; , Dr. Syamsul Hidayat, M.Ag (2015)
Modernism is a major theme of Western civilization. Western civilization was born because of European community was disappointed of Christian. Western civilization had taken inspiration philosophy of life of the Greeks, Romans, European countries, Jewish and Christian teachings. At first Western modernism appeared in Europe after the era of Renaissance. Western technological advances and their soul materialism encouraged them to be imperialist in out of-European countries, included Islamic countries. Then, Western imperialism comes successfully into a vehicle to spread Western modernism to their colony countries. Modernism then appears in the form of different levels, communism, socialism, capitalism, pragmatism, fascism, Nazism, kamalisme, Arab nationalism, Islamic nationalism. The responses of Muslims against Western modernism as an invation of Western thought to Islam, become various. Some refuse absolutely to modernism, in vice versa some receive absolutely, but some of them reject it and by the time accept the substance on which does not hit Islam itself. Maryam Jameelah thoughts about Western modernism becomes interesting, because she came from the Jewish race and was born in the United States, later she converted to Islam and became a Muslim intelectual as well. Based on the scope of the investigation, this thesis is included to the historical and social study. While on the method, this thesis is included to the research literature. Based on the type of research, it is included to a descriptive study. The approach of this study is an historical approach, sociological, theological or normative. The data sources are primary and secondary data. And the method of collecting data is by documentation. The analysis of this study is using Islamicworldview as a knife analysis to Maryam Jameelah thoughts about Western modernism. This study has found that Western modernism is misguided in the view of Islam. Western modernism that is anti-God, anti-revelation, and anti-Prophet is anti-religious view of life, and so that it is anti-Islam. Western modernism which contains of view materialism, will deliver destructions of human life in the case of faith, worship, social, and moral. The universe will be the target of mental greed because of Western modernism. So, science and technology from the West, must be Islamisied to be free from the values of Western modernism. There must be a process of adoption and adaptation. Islam as a revealation and civilization religion is original and never changes because of the course of history. Normatively, empirically, and historically Islam promises to rise again to dominate the world and enlighten it.